2016
DOI: 10.1080/15592324.2016.1238548
|View full text |Cite
|
Sign up to set email alerts
|

Wound signaling: The missing link in plant regeneration

Abstract: Wounding is the first event that occurs in plant regeneration. However, wound signaling in plant regeneration is barely understood. Using a simple system of de novo root organogenesis from Arabidopsis thaliana leaf explants, we analyzed the genes downstream of wound signaling. Leaf explants may produce at least two kinds of wound signals to trigger short-term and long-term wound signaling. Short-term wound signaling is primarily involved in controlling auxin behavior and the fate transition of regenerationcomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Here, we summarize the four steps of cell fate transition involved in direct DNRR from leaf explants together with adventitious rooting in other systems (Figure 1G ). In the first step “priming,” the endogenous auxin is transported into regeneration-competent cells (i.e., procambium and vascular parenchyma cells) in the vasculature near the wound and activates WUSCHEL-RELATED HOMEOBOX11 ( WOX11 ) expression for the fate transition from regeneration-competent cells to root founder cells (Liu et al, 2014 ; Chen et al, 2016a , b ). In the second step “initiation,” WOX11 and auxin coordinately activate WOX5 and LATERAL ORGAN BOUNDARIES DOMAIN16 ( LBD16 ) expression for the fate transition from root founder cells to root primordium (Liu et al, 2014 ; Hu and Xu, 2016 ; Sheng et al, 2017 ).…”
Section: Cell Fate Transition During Direct Dnrrmentioning
confidence: 99%
“…Here, we summarize the four steps of cell fate transition involved in direct DNRR from leaf explants together with adventitious rooting in other systems (Figure 1G ). In the first step “priming,” the endogenous auxin is transported into regeneration-competent cells (i.e., procambium and vascular parenchyma cells) in the vasculature near the wound and activates WUSCHEL-RELATED HOMEOBOX11 ( WOX11 ) expression for the fate transition from regeneration-competent cells to root founder cells (Liu et al, 2014 ; Chen et al, 2016a , b ). In the second step “initiation,” WOX11 and auxin coordinately activate WOX5 and LATERAL ORGAN BOUNDARIES DOMAIN16 ( LBD16 ) expression for the fate transition from root founder cells to root primordium (Liu et al, 2014 ; Hu and Xu, 2016 ; Sheng et al, 2017 ).…”
Section: Cell Fate Transition During Direct Dnrrmentioning
confidence: 99%
“…The increase in TSS in T2 and T3, being abrupt between 60 and 90 days can be explained by the fact that the bulbs of these treatments were collected with natural popping, indicating, theoretically, physiological maturity. The accumulation of sugars in this case would serve as an energy source for onion regrowth [29,30,31], explaining the accumulation at the end of storage. Non-structural sugars represent an important carbohydrate reserve in most onion bulbs and are generally enzymatically hydrolyzed to fructose during the storage period and are responsible for the concomitant increase in fructose concentration.…”
Section: Resultsmentioning
confidence: 90%
“…In addition to energy transfer in plants, carbohydrates are also involved in the regulation of gene expression [28]. Starch or any other carbohydrate from the raffinose group was not detected on onions [29]. The reduction in TSS of T1 during storage is due to the increased catabolism of carbohydrates by respiration, due to the stress caused by the manual tipping of the pseudo-stems.…”
Section: Resultsmentioning
confidence: 99%
“…One of the primary events of the response to wounding that occur at the wounded site is the burst of JA (Savatin et al, 2014;Chen et al, 2016a;Hilleary and Gilroy, 2018). Our GO analyses revealed that SPL10 represses JA signaling and biosynthesis during root regeneration.…”
Section: Convergence Of Age and Wound Signals On A Subset Of Ap2/ Erfsmentioning
confidence: 84%